New cerium(IV)-substituted hydroxyapatite nanoparticles: Preparation and characterization. Issue 9 (November 2015) - Ciobanu, Gabriela; Maria Bargan, Ana; Luca, Constantin
Abstract: Hydroxyapatite and new cerium(IV)-substituted hydroxyapatite nanoparticles were synthesized by the co-precipitation method from aqueous solutions of various Ce/(Ce+Ca) atomic ratios ranging from 0 to 0.25. The structural properties of the hydroxyapatite powders were characterized by scanning electron microscopy (SEM) coupled with X-ray analysis (EDX), X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), Fourier Transform Infrared spectroscopy (FTIR) and Brunauer–Emmett–Teller (BET) surface area analysis. The results confirm that cerium ions in the +4 as well as in the +3 states have been incorporated into the hydroxyapatite lattice. The (Ce+Ca)/P atomic ratio in the Ce-substituted hydroxyapatite samples was around 1.67. The prepared nanocrystalline powders consisted of hydroxyapatite as single crystallized phase with hexagonal structure and an average particle size of 20–60 nm. The antibacterial properties of cerium-substituted hydroxyapatite powders against Escherichia coli and Staphylococcus aureus bacteria were found to increase with increasing cerium content, being more effective against E. coli .